Estimación de Parámetros Para Cargas Contaminantes Conectadas a las Redes de Distribucción - Guerra, Pedro Raúl De León (KnE Engineering, 2018)
In this paper we propose a new algorithm for the estimation of the parameters of the harmonic loads connected to the electric distribution system. The new parameter estimation algorithm is based on the weighted least-squares technique. The estimation algorithm solves an optimization problem and minimizes a set of variables which must comply with a series of specifications or characteristics of the harmonic loads. The estimation algorithm is able to obtain a load model with good accuracy comparatively to current -model of the system, due to a good engineering estimation of the initial conditions. Finally the new estimation algorithm could be used for power quality studies and to measure the contribution of the harmonic contamination of the clients connected to the electrical distribution system. Keywords: Harmonics, parameter estimation, weighted least squares, models.